Pharmacognostic, Physicochemical Standardization and Phytochemical Analysis of leaves of Cultivated Crotalaria lachnosema Stapf. - Jemilat A. Ibrahim, Opeoluwa Makinde and Nneka N. Ibekwe (Journal of Applied Pharmaceutical Science)
Towards authentication and quality assurance of medicinal plants, pharmacognostic, physicochemical and preliminary phytochemical studies of the leaves of Crotolaria lachnosema Stapf. were carried out. The macroscopic and microscopic evaluation revealed characters that are of diagnostic value and useful in authentication of the plant. The Physicochemical analyses reveals values for moisture content, alcohol extractive, water extractive and total ash which are within the World Health Organisation (WHO) standards for crude drug from medicinal plants. Phyto-screening for secondary metabolites revealed the presence of saponins, terpenes/steroids, flavonoids, resins and balsams, while alkaloids, glycosides and tannins were absent. Information obtained from these studies can be used as markers in the identification and standardization of this plant as a herbal remedy and also towards monograph development on the plant.
Keywords: Authentication, chromatograph, Macroscopic, Microscopic